On some properties of dissipative functional differential inclusions in a Banach space - Obukhovskiĭ, Valeri; Zecca, Pietro (Topological Methods in Nonlinear Analysis, 2000)
For a semilinear functional differential inclusion of the form y’(t) Ay(t0+f(t, x_t) satisfying a dissipativity condition in a separable Banach space we prove the existence of a periodic solution and a global compact attractor.